Exploring the linear and quadratic effects of customer and competitor orientation on export performance - Lengler, J.; Sousa, C.; Marques, C. (International Marketing Review, 2013)
Purpose – Despite some attempts to integrate the market orientation construct into the international marketing area, most conceptual and empirical studies have been conducted in the context of domestic operations. In addition, few studies have examined the quadratic effects of customer and competitor orientation on export performance. To address this gap in the literature we test a model that examines whether customer and competitor orientation have linear or quadratic relationships with export performance. We also investigate if competitive intensity moderates the linear and quadratic relationships between customer and competitor orientation and export profit. Design/methodology/approach – The hypotheses are tested using survey data collected from 197 Brazilian export firms. Structural equation modeling was conducted to test the hypothesized relationships and to validate the proposed conceptual model. Findings – Empirical evidence reveals that, while customer orientation has a U-shaped relationship with export sales, the competitor orientation–export profit relationship is linear. Our results also provide evidence that the positive quadratic relationship between customer orientation and export profit is mediated by export sales. Contrary to expectations, the results also indicate that none of the linear or quadratic relationships investigated in the model are moderated by competitive intensity. Originality/value – We test a model in an export context that examines whether the relationships between the separate components of market orientation and export performance are linear or quadratic. We also contribute to the literature by examining these relationships in the context of a developing country, namely Brazil.